2008
DOI: 10.5650/jos.57.23
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Effective Dose on Serum Cholesterol Concentration and the Safety Evaluation of Dressing Containing Plant Sterol in Japanese Subjects

Abstract: We examined the minimal effective dose on serum cholesterol concentration and the safety of dressing containing plant sterol in humans. Exp.1: Sixty-eight healthy Japanese males (total cholesterol (TC) 170 mg/dL) were randomly divided into four groups, and were given 0, 400, 800 or 1200 mg/day of plant sterol in 15 g dressing for 4 weeks followed by the washout period of 4 weeks. Although there were no significant differences in serum TC and low-density lipoprotein cholesterol (LDL-C) concentrations among all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…For example, studies by Hendriks et al (1999) and Jakulj et al (2005) were not included in our analyses due to the lack of baseline values of liver enzymes. However, the results in these two studies were in line with our results, and did not find any significant relationship between Phytosterol supplementation and liver enzymes (Hendriks et al , 1999; Seki et al , 2003; Richter et al , 1996; Kurokawa et al , 2008; Jakulj et al , 2005; Derosa et al , 2018; Christiansen et al , 2001; Hsu et al , 2017; Gylling et al , 2010). Conversely other studies have reported contradictory results to that reported in our study.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…For example, studies by Hendriks et al (1999) and Jakulj et al (2005) were not included in our analyses due to the lack of baseline values of liver enzymes. However, the results in these two studies were in line with our results, and did not find any significant relationship between Phytosterol supplementation and liver enzymes (Hendriks et al , 1999; Seki et al , 2003; Richter et al , 1996; Kurokawa et al , 2008; Jakulj et al , 2005; Derosa et al , 2018; Christiansen et al , 2001; Hsu et al , 2017; Gylling et al , 2010). Conversely other studies have reported contradictory results to that reported in our study.…”
Section: Discussionsupporting
confidence: 90%
“…Eighteen studies reported the effect of Phytosterol supplementation on liver function. Among the included studies one study, used two doses of Phytosterol (Hironaka et al , 2006) and two used three doses (Kurokawa et al , 2008; Davidson et al , 2001)and we considered as separate studies. These studies were published between 1996 and 2018.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations